Review: Manufacturing Of Magnesium Oxide Nanoparticles As Antibacterial Agents - Asep Nandiyanto; Risti Ragadhita; Citra Nurhashiva; Tedi Kurniawan (Institute of Computer Science (IOCS), 2021)
The purpose of this article is to determine the most efficient synthesis method of magnesium oxide nanoparticles as an antimicrobial. The magnesium oxide synthesis method discussed in this study is complemented by the results of the study of the material sources, methods, advantages, and disadvantages of each method so that it can be a reference for choosing which method is more efficient in the synthesis of magnesium oxide. synthesis of magnesium oxide such as (1) synthesis of plant extracts,(2)) combustion, (3) sonochemical synthesis, (4) sol-gel synthesis, and (5) solid-state taken from the journal 2017-2020. This synthesis method resulted in the characterization of magnesium oxide nanoparticles which were analyzed using X-ray Diffraction (XRD), Fourier Transform Infra-Red (FTIR), Field Emission Scanning Electron Microscopy (FESEM). The results showed that there were advantages and disadvantages of each method of synthesis of magnesium oxide used. The most efficient method for synthesizing magnesium oxide as an antimicrobial is the sol-gel synthesis method. The sol-gel method uses readily available materials, has a relatively low cost, easy procedure to perform, and was found to be a light and efficient route for large-scale industrial production of fine magnesium oxide nanoparticles as antimicrobials.